ANALISIS CAMPURAN ASPAL AC-BC PG 76 DENGAN ADDITIONAL FILLER ABU BAMBU TERHADAP STABILITAS DAN KEPADATAN ASPAL - Dwi Yanti; Farlin Rosyad; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This research is an experimental study aimed at investigating the effect of bamboo ash filler on the characteristics of Asphalt Concrete-Binder Course (AC-BC) using PG 76 hard asphalt. The variations of bamboo ash filler used were 0%, 0.5%, 1%, 1.5%, and 2% of the total filler weight. The tests conducted included the Marshall test to obtain stability, flow, VIM, VMA, VFB, and density parameters. The results indicate that the addition of bamboo ash as a filler affects the characteristics of the mixture. The stability values still meet the 2018 Bina Marga specifications (revision 3), although a decrease was observed at certain levels. Bulk density fluctuated with the addition of filler, while VIM, VMA, and VFB values changed according to the bamboo ash content. Overall, bamboo ash can be considered as an alternative filler in AC-BC mixtures, provided that the optimum content is maintained to avoid reducing the mixture’s performanceKeywords: filler, bamboo ash, AC-BC, PG 76 asphalt, Marshall